SPECT Imaging of P. aeruginosa Infection in Mice Using 123I-BMIPP - Yuri Nishiyama; Asuka Mizutani; Masato Kobayashi; Yuka Muranaka; Kakeru Sato; Hideki Maki; Keiichi Kawai (MDPI AG, 2024)
Pseudomonas aeruginosa infection is an infectious disease that must be controlled because it becomes chronic and difficult to treat, owing to its unique system of toxin production/injection and elimination of other bacteria. Here, we noninvasively monitored P. aeruginosa using single-photon emission computed tomography (SPECT) imaging. Determining the amount and localization of the P. aeruginosa will enable making faster clinical diagnoses and selecting the most appropriate therapeutic agents and methods. Nonclinically, this information can be used for imaging in combination with biofilms and toxin probes and will be useful for discovering drugs targeting P. aeruginosa. To study P. aeruginosa accumulation, we conducted in vitro and in vivo studies using iodine-123 β-methyl-p-iodophenyl-pentadecanoic acid (123I-BMIPP), which we previously reported using for Escherichia coli. In vitro, 123I-BMIPP accumulated in P. aeruginosa by being taken up into the bacteria and adsorbing to the bacterial surface. In vivo, 123I-BMIPP accumulated significantly more in infected sites than in noninfected sites and could be quantified by SPECT. These results suggest that 123I-BMIPP can be used as a probe for P. aeruginosa for SPECT. Establishing a noninvasive monitoring method using SPECT will allow further progress in studying P. aeruginosa.